On the Flow of Generalized Burgers' Fluid Induced by Sawtooth Pulses - Qamar Sultan; mudassar nazar; Usman Ali; Ikhlaq Ahmad (Journal of Applied Fluid Mechanics, 2015)
This paper presents a study for the MHD flow of an incompressible generalized Burgers' fluid through a rectangular duct in porous medium. The flow is generated due to the velocity sawtooth pulses applied on the duct. Exact solutions of the governing equations are obtained by using the Laplace transform and double finite Fourier sine transform in this order. The obtained solutions satisfy all the initial and boundary conditions and are written as a sum of steady and transient solutions. Graphs are plotted for both developing and retarding flows. The effects of magnetic parameter, porosity parameter, and various parameters of interest on the flow characteristics are discussed. The problem reduces to the flow between two plates in the absence of side walls.